(untitled) (World Bulletin of Social Sciences, 2021)
Knowledge of physical and environmental education is learned as the main idea of the scientific-methodological concept of "Physical education as a means of student health" to offer physical activity as a means of student health, systematization in the educational process, conditions in the article. In addition, the relevant skills of many professionals, schoolchildren in the formation of a healthy lifestyle are also described.